2019
DOI: 10.1093/jxb/erz487
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel regulation of endoplasmic reticulum stress responses in plants: where old roads and new paths meet

Abstract: The sessile lifestyle of plants requires them to cope with a multitude of stresses in situ. In response to diverse environmental and intracellular cues, plant cells respond by massive reprogramming of transcription and translation of stress response regulators, many of which rely on endoplasmic reticulum (ER) processing. This increased protein synthesis could exceed the capacity of precise protein quality control, leading to the accumulation of unfolded and/or misfolded proteins that triggers the unfolded prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…The extensive influence of tRNA thiolation defects on protein homeostasis would trigger chronic proteotoxic stress 27 . Previous studies have shown that protein-synthesis defects in the URM1 pathway mutants in yeast led to the production of misfolded or error-containing proteins 27,46 , which triggered endoplasmic reticulum stress, thus activating downstream signaling pathways involved in abiotic-stress responses 46,48 . Similarly, our proteomic analysis also revealed the accumulation of five proteins (TrEMBL UniProt ID: Q6ZFJ9, Q651B0, Q653F6, Q6Z2M2, and Q9LWT6) in the slg1 mutant (Supplementary Data 2), these proteins appear to be involved in unfolded protein binding and chaperone-mediated protein folding.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive influence of tRNA thiolation defects on protein homeostasis would trigger chronic proteotoxic stress 27 . Previous studies have shown that protein-synthesis defects in the URM1 pathway mutants in yeast led to the production of misfolded or error-containing proteins 27,46 , which triggered endoplasmic reticulum stress, thus activating downstream signaling pathways involved in abiotic-stress responses 46,48 . Similarly, our proteomic analysis also revealed the accumulation of five proteins (TrEMBL UniProt ID: Q6ZFJ9, Q651B0, Q653F6, Q6Z2M2, and Q9LWT6) in the slg1 mutant (Supplementary Data 2), these proteins appear to be involved in unfolded protein binding and chaperone-mediated protein folding.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that ER stress and UPR were not within the enriched GO terms, we identified the upregulation of genes related to both processes at the presymptomatic stage ( Supplementary Table 7 ). Upon stress conditions, the accumulation of unfolded/misfolded proteins in the ER triggers the UPR, a protective response that improves protein folding activity and removes proteins from the ER ( Afrin et al., 2020 ). When the relief of the ER stress fails, the programmed cell death can be activated ( Eichmann and Schäfer, 2012 ; Williams et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The heat stress response has formed as a result of natural selection, improving the capacity of cells, organisms, and populations to withstand situations that require action. In eukaryotic cells, heat exposure triggers a multitude of responses that collectively upregulate a suite of molecular chaperones, such as Heat Shock Proteins (HSPs), to assist with protein folding and stress recovery, maintaining cell viability and ensuring robustness (Gardner et al, 2013;Afrin et al, 2020). While such adaptive responses may be triggered at moderately increased temperatures without leading to a change of cells' fate, a true resilience-based response will allow the cell to cope with heat shock perturbation, recover, and develop tolerance to the next perturbation (Smirnova et al, 2015).…”
Section: Robustness and Resilience Of Heat Stress Responses Across Scmentioning
confidence: 99%